Implementasi Activity Based Costing Sebagai Alternatif Perhitungan Biaya Program Bimbingan Belajar Pada Lembaga XYZ - Ladista, Rindy Dwi; Maryani, Ani; Febriani, Erni (Universitas Mitra Indonesia, 2024)
The use of traditional methods make cost distortions. This research was conducted to provide an alternative for calculating the cost of the tutoring program at D'Premier9 so that the resulting costs are more accurate and able to describe the consumption of relevant resources according to the activities. The research was conducted with a case study on D'Premier9, by calculating the cost assignment using the Activity Based Costing method. The results showed that there was a cost distortion due to the use of the traditional cost method, in the Polri program an undercost of Rp. 403,848 while the service program costs experienced an overcost of Rp. 302,886. The calculation with the traditional method make cost distortions because the assignment is not carried out according to the cost driver, but by using ABC the cost calculation is more accurate because it calculates the cost driver.